Impoliteness Strategies in the Doracimin Animation on YouTube (A Pragmatic Study) - Nurika Rizka Salsabila (Sabda: Jurnal Kajian Kebudayaan, 2026)
AbstractThis research aims to describe the forms of impoliteness strategies and functions in the utterances of characters in the Doracimin animated series. The theoretical framework employed is Jonathan Culpeper's theory of impoliteness. This research uses a qualitative and descriptive research design. Data were collected using the observation method and note-taking technique. The observation method was conducted by closely watching short animated videos of Doracimin, followed by note-taking technique to record the data and mark them according to the identified types of impoliteness. The data were analyzed using the pragmatic padan method with the constituent analysis technique. The research procedure consisted of four stages: data collection, data reduction, data presentation, and data verification. The results of the data analysis are presented informally through narrative descriptions. The findings of the study reveal that the characters' utterances in Doracimin contain complex impoliteness strategies and functions. The strategies identified include superstrategies such as bald on-record impoliteness, positive impoliteness, negative impoliteness, off-record impoliteness, and withhold politeness, as well as a metastrategy in the form of sarcasm or mock politeness. The functions of impoliteness identified in the data include affective, coercive, and entertainment functions. The entertainment function reflects various types of pleasure, namely emotional pleasure, aesthetic pleasure, voyeuristic pleasure, the pleasure of being superior, and the pleasure of feeling secure.Keywords: impoliteness, impoliteness strategies, functions of impoliteness, pragmatics, Doracimin animated series AbstrakPenelitian ini bertujuan untuk mendeskripsikan bentuk strategi dan fungsi ketidaksantunan dalam tuturan para tokoh animasi Doracimin. Teori yang digunakan adalah teori ketidaksantunan Jonathan Culpeper. Jenis penelitian ini adalah penelitian kualitatif dan penelitian deskriptif. Pengumpulan data menggunakan metode simak dan teknik catat. Metode simak dilakukan dengan menyimak video pendek animasi Doracimin, dilanjutkan teknik catat dengan mencatat data dan memberi penanda sesuai jenis ketidaksantunan. Analisis data menggunakan metode padan pragmatis dengan teknik pilah unsur penentu (PUP). Prosedur penelitian terdiri atas empat tahap, yaitu pengumpulan data, reduksi data, penyajian data, dan verifikasi data. Hasil analisis data disajikan dengan metode informal dalam bentuk uraian naratif. Hasil penelitian membuktikan bahwa tuturan antartokoh dalam animasi Doracimin mengandung strategi dan fungsi ketidaksantunan yang kompleks. Strategi yang ditemukan meliputi superstrategi berupa bald on-record impoliteness (ketidaksantunan langsung), positive impoliteness (ketidaksantunan positif), negative impoliteness (ketidaksantunan negatif), off-record impoliteness (ketidaksantunan tersamar), withhold politeness (menahan kesantunan) dan metastrategi berupa sarcasm or mock politeness (sarkasme atau kesantunan semu). Fungsi ketidaksantunan yang teridentifikasi mencakup fungsi afektif, koersif, dan hiburan. Fungsi hiburan mencerminkan berbagai bentuk kenikmatan, yaitu kenikmatan emosional, kenikmatan estetis, kenikmatan voyeuristik, kenikmatan karena merasa superior, dan kenikmatan karena merasa aman.Kata Kunci: ketidaksantunan, strategi ketidaksantunan, fungsi ketidaksantunan, pragmatik, animasi Doracimin